EFFECT OF LIQUIDITY MANAGEMENT, ASSET MANAGEMENT, DEBT MANAGEMENT ON PROFIT - Dwi Urip Wardoyo; Nurul Melati; Mega Oktavianta (Globalwriting Academica Consulting & Publishing, 2021)
Profitability Impact of Liquidity Management, Asset Management, and Debt Management. The goal of this study is to develop a multiple linear regression model for use as an earnings estimator. This study looks at mining firms that were listed on the IDX between 2017 and 2020, have audited financial statements, and generate profits throughout that time period. Current Ratio (CR), Total Assets Turnover Ratio (TATO), and Debt Ratio (DR) are used as independent variables in this study. This variable is used to denote the management of liquidity, assets, and debt. Meanwhile, the dependent variable utilized as a surrogate for profit is the Return on Assets Ratio (ROA). The findings indicate that liquidity, asset, and debt management all have a major impact on earnings.